Two new quill mites of the family Syringophilidae (Acari: Prostigmata) parasitising the tapaculos (Passeriformes: Rhinocryptidae) in South America - Sikora, Bozena; Kaszewska, Katarzyna; Skoracki, Maciej (Zootaxa, 2014)
Two new species of syringophilid mites (Acari: Prostigmata: Syringophilidae) associated with passeriform birds of the family Rhinocryptidae in South America are described: Syringophiloidus teledromas sp. nov. from Teledromas fuscus (Sclater and Salvin) in Argentina and Aulonastus pteroptochos sp. nov. from Pteroptochos tarnii (King) in Chile. The genus Aulonastus Kethley, 1970 is recorded from the tapaculos for the first time, and the new species of Syringophiloidus Kethley, 1970 described here is the second record of this genus on rhinocryptid birds.